2014
DOI: 10.1007/s40273-014-0236-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Rivaroxaban for Stroke Prevention in German Patients with Atrial Fibrillation

Abstract: Our results showed that the substantially higher medication costs of rivaroxaban were offset by mitigating the shortcomings of warfarin, most notably frequent dose regulation and bleeding risk. Future health economic studies on novel oral anticoagulants should evaluate the cost effectiveness for secondary stroke prevention and, as clinical data from direct head-to-head comparisons become available, new anticoagulation therapies should be compared against each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 79 publications
(98 reference statements)
1
10
0
Order By: Relevance
“…Our results in NVAF patients are more favourable for rivaroxaban compared to results from other studies performed in Belgium and Germany 35,36 . This might be caused by the fact that the other studies are both only based on the clinical trial data from the ROCKET-AF study and that RWD shows a more positive outcome for rivaroxaban.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our results in NVAF patients are more favourable for rivaroxaban compared to results from other studies performed in Belgium and Germany 35,36 . This might be caused by the fact that the other studies are both only based on the clinical trial data from the ROCKET-AF study and that RWD shows a more positive outcome for rivaroxaban.…”
Section: Discussionsupporting
confidence: 54%
“…Another explanation could be that the drug costs of rivaroxaban have decreased substantially since these studies were published. This is a major contributor to the cost of the treatment and, for our study, we have used a cost of e2.16 per 20 mg rivaroxaban, whereas the Belgian and German studies used e2.70 and e3.26, respectively 29,35,36 . The use of e2.16 in this study is based on data from the Dutch Healthcare institute, which shows the price before a discount is agreed upon by the government and the manufacturer 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was for the analysis for the Greek setting where the total lifetime cost was found lower for rivaroxaban treatment resulting in a cost saving of e239 17 . The number of QALY was found higher for the rivaroxaban treatment compared to the warfarin treatment [8][9][10][11][12][13][14][15][16][17] . Rivaroxaban treatment was found to be cost-effective compared to the warfarin treatment in those studies [8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 89%
“…It also has less drug-drug and drug-food interactions than warfarin. Although previous analyses in other countries indicated that rivaroxaban is more cost-effective compared to warfarin [8][9][10][11][12][13][14][15][16][17] . Clinical practices in Japan such as lower anticoagulation targets, healthcare costs and efficacy and safety of rivaroxaban in the Japanese population are different from other countries.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation